Research on Tension Distributed Characteristic of Scraper Chain based on State Observer - Xing Zhang; Fan Jiang; Chenxi Jia; Yutan Li; Chuanjin Zhang (Jixie chuandong)
Aiming at the structural complexity of chain drive system and the difficulty in tension distribution analysis of the scraper chain，the tension distributed characteristics of the scraper chain are studied based on the design of state observer.A chain-drive virtual prototype model is constructed by the Adams simulation software，and the discrete mathematical model of the chain drive system is then established based on the finite element analysis.Through design of the state observer，the estimation of tension distribution of the scraper chains is accomplished，so as to provide an effective basis for the operation status assessment of the scraper conveyor.